Non-linear behaviour of concrete beams reinforced with GFRP and CFRP bars grouted in sleeves. (February 2020) - Kazemi, Mostafa; Li, Jie; Lahouti Harehdasht, Salar; Yousefieh, Negin; Jahandari, Soheil; Saberian, Mohammad
Abstract: The low-quality bond between fibre reinforced polymer (FRP) bars and surrounding concrete has drawn the attention of many researchers. The use of high-strength materials such as the grout in the intersection of FRP bars and surrounding concrete can effectively prevent any slippage once they are in contact and subsequently increase the bond quality. Therefore, this study was numerically focused on the flexural behaviour of concrete beams reinforced with glass fibre reinforced polymer (GFRP) and carbon fibre reinforced polymer (CFRP) bars, grouted only in the pure bending zone and along the whole beam length. The numerical outputs revealed that the grouted GFRP bars propagated the maximum principal stress in high-strength concrete beams, but not as much as that in normal-strength concrete specimens. In addition, the stress distribution in the grout, created only in the pure bending zone, was nearly constant at the ultimate moment. For the grout, developed along the whole beam length, this stress increased by approaching the mid-span of the concrete beam. Furthermore, at the ultimate moment, the tensile stress of 12-mm diameter CFRP bars was about 3.5 times more than that of the 16-mm diameter CFRP bars, leading to the generation of difference between failure modes of concrete specimens reinforced with various diameters of CFRP bars.